Smart Nanotherapeutics and Lung Cancer - Mohammad Doroudian; Mohammad H. Azhdari; Nima Goodarzi; David O'Sullivan; Seamas C. Donnelly (MDPI AG, 2021)
Lung cancer is a significant health problem worldwide. Unfortunately, current therapeutic strategies lack a sufficient level of specificity and can harm adjacent healthy cells. Consequently, to address the clinical need, novel approaches to improve treatment efficiency with minimal side effects are required. Nanotechnology can substantially contribute to the generation of differentiated products and improve patient outcomes. Evidence from previous research suggests that nanotechnology-based drug delivery systems could provide a promising platform for the targeted delivery of traditional chemotherapeutic drugs and novel small molecule therapeutic agents to treat lung cancer cells more effectively. This has also been found to improve the therapeutic index and reduce the required drug dose. Nanodrug delivery systems also provide precise control over drug release, resulting in reduced toxic side effects, controlled biodistribution, and accelerated effects or responses. This review highlights the most advanced and novel nanotechnology-based strategies, including targeted nanodrug delivery systems, stimuli-responsive nanoparticles, and bio-nanocarriers, which have recently been employed in preclinical and clinical investigations to overcome the current challenges in lung cancer treatments.